Tingkat Kenyamanan Termal Ruang Terbuka Hijau dengan Pendekatan Temperature Humidity Index (THI) - Siva Devi Azahra; Siti Masitoh Kartikawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to examine the level of thermal comfort of Tanjungpura University's green open space. The method used is to measure air temperature and humidity at seven green open spaces with three observation periods and then analyze it by calculating the Temperature Humidity Index (THI) value at each location. The results showed that the overall thermal comfort of green open space was still in the uncomfortable and partially uncomfortable category, with THI values between 25.61 to 28.93. In conclusion, there is a need for the development and enrichment of green open space vegetation in the Tanjungpura University area to increase thermal comfort for the academic community. Keywords: Thermal Comfort, Green Open Space, Temperature Humidity Index